2015
DOI: 10.1186/s40677-015-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of landslide over erodible surface

Abstract: Background: Estimating the magnitude and intensity of landslides is a fundamental requirement in quantitatively evaluating the risks involved, and preparing a mitigation strategy. Though the physics-based dynamic model of landslide can predict the travel distance, kinematic velocity, and hazard zone, the effects of erosion and the excess pore water pressure during the dynamic process of landslide are often ignored. Results: In order to study these factors, a physics-based dynamic model of landslide considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The final debris flow volume after erosion can be as much as 50 times that of the debris flow start volume. The influence of erosion on the volume of the debris flow, impact of the debris flow, and its structure have been verified by numerical simulation and physical simulation experiments done by Haas and Woerkom [14], Liu et al [15], and Tian et al [16]. Shen et al [6], Mangeney et al [12], Haas and Woerkom [14], Mangeney et al [17], and Egashira et al [18] conducted field observations and physical simulation experiments to reproduce the process of detrital flow on soil erosion and systematically study the factors which influenced erosion.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…The final debris flow volume after erosion can be as much as 50 times that of the debris flow start volume. The influence of erosion on the volume of the debris flow, impact of the debris flow, and its structure have been verified by numerical simulation and physical simulation experiments done by Haas and Woerkom [14], Liu et al [15], and Tian et al [16]. Shen et al [6], Mangeney et al [12], Haas and Woerkom [14], Mangeney et al [17], and Egashira et al [18] conducted field observations and physical simulation experiments to reproduce the process of detrital flow on soil erosion and systematically study the factors which influenced erosion.…”
Section: Introductionmentioning
confidence: 71%
“…Shen et al [6], Mangeney et al [12], Haas and Woerkom [14], Mangeney et al [17], and Egashira et al [18] conducted field observations and physical simulation experiments to reproduce the process of detrital flow on soil erosion and systematically study the factors which influenced erosion. Liu et al [15] adopted the finite volume method to simulate the landslide dynamic model considering erosion and excess pore water pressure, while Li and Zhao [19] adopted the CFD-DEM numerical analysis method to study the erosion and mass exchange of debris flow. This research showed that the amount of soil erosion is positively correlated with the slope of the channel and the solid-liquid ratio and also that the fluidity and the impact force of debris flow may increase due to mass exchange.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…e impact-induced liquefaction during the sliding process is probably the driving force behind the high speed and long runout of these landslides on nearhorizontal terraces [2,[19][20][21], but the mechanism of this effect is not yet well understood. Pore water pressure, which plays a crucial role in the liquefaction process, is most affected by the saturation of the soil [22]. erefore, in order to propose a liquefaction mechanism under impact, this paper focuses on the following three research objectives: (1) the development of pore water pressure under impact; (2) the liquefaction characteristics of sandy silt soils under the influence of saturation; and (3) the revealing of the mechanism of impact-induced liquefaction.…”
Section: Introductionmentioning
confidence: 99%